miR-200-3p suppresses cell proliferation and reduces apoptosis in diabetic retinopathy via blocking the TGF-β2/Smad pathway - Xue, Liping (Biosci Rep, 2020)
Increasing evidence has shown that microRNAs (miRNAs) play an important role in the pathogenesis of diabetic retinopathy (DR). However, the role and mechanism of miRNA in regulating high glucose (HG)-induced ARPE-19 cell injury are still not well understood. The present study aimed to investigate the effects of miR-200a-3p on DR progression and reveal the underlying mechanisms of their effects. In the present study, we observed that miR-200a-3p was significantly decreased, while transforming growth factor-β2 (TGF-β2) expression was up-regulated in ARPE-19 cells treated with HG and retina tissues of DR rats. Subsequently, overexpression of miR-200a-3p significantly promoted cell proliferation, reduced apoptosis, as well as inhibited the levels of inflammatory cytokines secreted, matrix metalloprotease 2/9 (MMP2/9), and vascular endothelial growth factor (VEGF) in HG-injured ARPE-19 cells. Moreover, miR-200a-3p was proved to target TGF-β2 mRNA by binding to its 3′ untranslated region (3′UTR) using a luciferase reporter assay. Mechanistically, overexpression of miR-200a-3p reduced HG-induced ARPE-19 cell injury and reduced inflammatory cytokines secreted, as well as down-regulated the expression of VEGF via inactivation of the TGF-β2/Smad pathway in vitro. In vivo experiments, up-regulation of miR-200a-3p ameliorated retinal neovascularization and inflammation of DR rats. In conclusion, our findings demonstrated that miR-200a-3p-elevated prevented DR progression by blocking the TGF-β2/Smad pathway, providing a new therapeutic biomarker for DR treatment in the clinic.